PENGARUH REPUTASI AUDITOR, AUDIT FEE DAN FIRM SIZE TERHADAP AUDIT DELAY (Studi Empiris pada Perusahaan Consumer Non-Cyclicals yang Terdaftar di Bursa Efek Indonesia Periode 2022-2024) - Andio, Rifki; Friyani, Rita; Dahlia, Dahlia (Jurnal Akuntansi Kompetif, 2026)
This study aims to analyze the effect of auditor reputation, audit fee, and firm size on audit delay in Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2022–2024. The phenomenon of audit delay has become an important concern, as the timeliness of financial statement submission serves as a key indicator of the quality of information for stakeholders. The research method employed is a quantitative approach using secondary data obtained from companies’ annual reports. The population includes all primary consumer goods companies, with the sample selected through purposive sampling. Based on these criteria, a total of 77 companies were obtained, resulting in 231 observations over a three-year period. The data analysis technique applied is multiple linear regression analysis using SPSS version 27. This study has fulfilled the classical assumption tests, including normality testing through visual analysis using histogram graphs and Normal P-P Plot. The results indicate that simultaneously, auditor reputation, audit fee, and firm size affect audit delay. Partially, auditor reputation and firm size do not affect audit delay. However, audit fee has a significant negative effect on audit delay, indicating that higher audit fees tend to accelerate the audit completion Keywords: Auditor Reputation, Audit Fee, Firm Size, Audit Delay, Consumer Non-Cyclicals.